Concrete ideas : material to shape a city - Petricone, Pina; Baird, George (London : Thames & Hudson, 2012)
This book explores the ways in which new technologies are changing concrete and the ways in which it is used. Through a series of montages, drawings and photographs, it visually speculates on concretes capacity as an urban catalyst, its potential for defining cities and the many ways in which it is being applied in urban renewal. With thoughtful, informed contributions from experts such as Mark West, George Baird, Will Bruder and Charles Waldheim, among others, and specially taken photographs of concrete buildings around the world (although Toronto features heavily as an exemplar of a successful concrete city), this book is key reading for all architecture students and practitioners, and offers a seductive argument for the reconsideration and reclamation of this age-old building material.
boek